2022
DOI: 10.36253/bae-12160
|View full text |Cite
|
Sign up to set email alerts
|

On the relationships among durum wheat yields and weather conditions: evidence from Apulia region, Southern Italy

Abstract: The weather index-based insurances may help farmers to cope with climate risks overcoming the most common issues of traditional insurances. However, the weather index-based insurances present the limit of the basis risk: a significant yield loss may occur although the weather index does not trigger the indemnification, or a compensation may be granted even if there has not been a yield loss. Our investigation, conducted on Apulia region (Southern Italy), aimed at deepening the knowledge on the linkages between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Agricultural insurance is an effective risk management tool that compensates farmers for post-disaster losses, contributing to the stability and continuity of agricultural production (Tappi et al 2022). Ardic et al (2013) reported the global stand on financial inclusion and found that high-income countries had ten times the deposit penetration as low-income countries.…”
Section: Financial Inclusion and Economic Growthmentioning
confidence: 99%
“…Agricultural insurance is an effective risk management tool that compensates farmers for post-disaster losses, contributing to the stability and continuity of agricultural production (Tappi et al 2022). Ardic et al (2013) reported the global stand on financial inclusion and found that high-income countries had ten times the deposit penetration as low-income countries.…”
Section: Financial Inclusion and Economic Growthmentioning
confidence: 99%
“…As a risk management tool, agricultural insurance effectively compensates for farmers' post-disaster losses and is conducive to the continuity and stability of agricultural production [ 28 ]. Many scholars have carried out research on agricultural insurance and its effects on household income, agricultural output and the rural economy [ [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%